What Are the Indicators of Student Engagement in Learning Management Systems? A Systematized Review of the Literature - Ahmadi, Golchehreh; Mohammadi, Aeen; Asadzandi, Shadi; Shah, Mahsood; Mojtahedzadeh, Rita (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2023)
Student engagement has an important role in academic achievement in all learning contexts, including e-learning environments. The extent of monitoring and promoting student engagement in e-learning affects the quality of education and is a determining factor for ensuring student’s success. Log data of students’ activities recorded in a learning management system (LMS) can be used to measure their level of engagement in the online teaching–learning process. No previous studies have been found stating a consistent and systematically raised list of LMS-based student engagement indicators, so this systematized review aimed to fulfill this gap. The authors performed an advanced search in the PubMed, Ovid, Google Scholar, Scopus, Web of Science, ProQuest, Emerald, and ERIC databases to retrieve relevant original peer-reviewed articles published until the end of June 2021. Reviewing the 32 included articles resulted in 27 indicators that were categorized into three themes and six categories as follows: (a) log-in and usage (referring to LMS, access to course material), (b) student performance (assignments, assessments), and (c) communication (messaging, forum participation). Among the categories, access to course material and messaging were the most and the least mentioned, respectively.